Telework during the COVID-19 pandemic: An approach from the perspective of Romanian enterprises - Mirela Cătălina Turkeș; Aurelia-Felicia Stăncioiu; Codruța Adina Băltescu (Amfiteatru Economic Journal, 2021)
The paper analyzes the impact of some decisional factors that shape telework in Romanian enterprises. These factors give us an image at macro and micro levels on the influences and changes that manifest themselves on the behavior of Romanian managers who, during the COVID-19 pandemic, were forced to resort to the organization of telework. The results obtained are a starting point in the development of a structural model. The research was conducted based on an online survey, the questionnaire being administered to a sample of 154 Romanian managers. The testing of the hypotheses of the structural modeling equations was performed using the least squares method, and the software used for data processing and analysis was SPSS 20 and SmartPLS3. The results of the study confirm the theoretical aspects illustrated throughout the article, capturing the mobility and adaptability of the behavior of Romanian managers in a crisis. Telework within Romanian enterprises is strongly and significantly influenced by the action of the factors analyzed in this paper, namely: work organization, performance management, safety and health at work, information security management, and digitalization. Modification of legal and contractual regulations is the only factor that has a weak and insignificant influence on telework.
Keywords: C12; C35; M31; M54; 330; telework; COVID-19 pandemic; decision makers; managers; enterprises